Drying shrinkage and porosity of polymer modified concrete containing vinyl acetate effluents - Noruzman, A.; Ismail, Mohamed; Yusuf, T.; Forouzani, P. (Universiti Putra Malaysia, Universiti Pertanian Malaysia Press, 2017)
The volume of waste generated from surface coating industries is of global concern. The disposal of this waste in the form of effluent has put enormous pressure on land and also poses as a health hazard when it leaches into soil and underground water. The study aims to examine the utilization of vinyl acetate effluents from water based paint factories as an admixture in concrete. Concrete specimens containing 0%, 2.5%, 5% and 10% of vinyl acetate effluents by weight of cement were prepared. The specimens were tested for drying shrinkage for 28 days and porosity was tested using mercury intrusion porosimetry. Findings show that concrete containing various proportions of vinyl acetate effluents manifests higher shrinkage behaviour compared to the control item. An investigation of pore size distribution reveals that polymer effluents have particles size larger than 50 nm which are categorize as macroporous in accordance to IUPAC classification. It can be concluded that adding polymer vinyl acetate effluents affects concrete deformation due to the condition of its pore structures. The utilization of this material may provide beneficial effect in terms of the durability performance of concrete and minimize environmental pollution.